CROWDFUNDING 2.0: THE RESURGENCE OF COVID-19 IN BRUNEI DARUSSALAM - Amnisuhailah Abarahan (Journal of Islamic, Social, Economics and Development, 2022)
The use of crowdfunding initiatives has taken a broad spectrum especially in the field of finance. It has enabled fund accumulations to be done in a swift and allocated manner for the said purpose it is collected in the first place. The manner of how this concept has evolved and served its purpose has been essential in the accumulation of funds particularly during the Covid-19 outbreak in Brunei Darussalam. The study investigates the reopening of the Covid-19 relief fund as a means of crowdfunding during the second wave in the country. This is a qualitative study based on the ongoing phenomena in Brunei Darussalam where data are sourced from media releases and press conferences made by the Ministry of Finance and Economy in relation to the fund. It is found that the response of Bruneians to contribute towards the reopening of the relief fund is at a slower pace compared to its first initiation. This shows that the consumer behaviour of donors during the second wave needs to be taken into consideration before the conclusion for the readiness of Bruneians on the concept of crowdfunding alike is suggested to be introduced into the country especially during times of need (darurah).The paper also provides important information on the link between the pandemic and voluntary fund raising initiatives for the progress of Islamic social finance in Brunei.